Human Reproductive and Prenatal Genetics - Leung, Peter C. K.; Qiao, Jie
Human Reproductive and Prenatal Genetics presents the latest material from a detailed molecular, cellular and translational perspective. Considering its timeliness and potential international impact, this all-inclusive and authoritative work is ideal for researchers, students, and clinicians worldwide. Currently, there are no comprehensive books covering the field of human reproductive and prenatal genetics. As such, this book aims to be among the largest and most useful references available.